A new species of Catapagurus A. Milne-Edwards (Crustacea: Decapoda: Anomura: Paguridae) from Brazil, with a key to the western Atlantic species - Nucci, Paulo Ricardo; de Melo, Gustavo Augusto Schmidt (Zootaxa, 2012)
We describe herein a new species of Catapagurus, the twenty-second species of the genus. This is the third species ofCatapagurus recorded from the western Atlantic and the second from Brazil; the remaining 19 species occur in the IndoPacific region.